2019
DOI: 10.1155/2019/8369179
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Production by Rhodospirillum rubrum Using a Two-Step Culture Strategy

Abstract: Polyhydroxyalkanoates (PHAs) are microbially synthesized biopolyesters which have attracted great attentions as a new biological material, potential alternative to traditional fossil fuel-based plastic due to their biodegradability and biocompatibility. Poly-3-hydroxybutyrate (PHB) and poly-(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) are the most common members of PHAs. In this study, the nonsulfur and facultatively phototrophic bacterium Rhodospirillum rubrum was cultivated to accumulate PHA by a two-step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…AARL T020, two-stage cultivation was shown to facilitate maximal biomass yield. This strategy demonstrates the noteworthy capabilities of PHBV production, not only in cyanobacteria but also in bacteria, as previously reported [ 57 ]. Furthermore, this strategy could be implemented in the production of several secondary metabolized substances, such as astaxanthin in Haematococcus pluvialis JNU35, extracellular polymeric substances (EPS) in Arthrospira sp., docosahexaenoic acid in Crypthecodinium cohnii , and lipid production in Dunaliella tertiolecta [ 58 , 59 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 82%
“…AARL T020, two-stage cultivation was shown to facilitate maximal biomass yield. This strategy demonstrates the noteworthy capabilities of PHBV production, not only in cyanobacteria but also in bacteria, as previously reported [ 57 ]. Furthermore, this strategy could be implemented in the production of several secondary metabolized substances, such as astaxanthin in Haematococcus pluvialis JNU35, extracellular polymeric substances (EPS) in Arthrospira sp., docosahexaenoic acid in Crypthecodinium cohnii , and lipid production in Dunaliella tertiolecta [ 58 , 59 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 82%
“…An Increase in 3HV content results in an increase in the amorphous phase and thus leads to a reduction in X c and T c [ 48 ]. A lower T c indicates that the complete crystallization takes a longer time [ 49 ]. PHBV-15 has the lowest 3HV content (0.16), high X c (29%), and low T c of 62 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Higher PDI indicates a larger size distribution of polymer chains. Shorter chains need less time for crystallization compared to longer chains which results in reduction of T c [ 49 ]. A T c value ranging from 41 to 82 °C for CHCl 3 extracted PHBV with 3HV contents of (20–60%) have been reported [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been demonstrated that the PNSB Rhodospirillum Rubum synthetizes PHBV from sugars and wastes without the need of precursors supply (Smith et al 2008;Liu et al 2019). In particular, in a study from Liu et al (2019), a 46.5% 3HV fraction was observed, which was the highest obtained in all the reviewed studies from unrelated carbon sources.…”
Section: Wild Speciesmentioning
confidence: 97%